Design and Construction of a Current and Voltage Monitoring System as an Indicator of Disturbances in IoT-Based Runway Edge Lights - Saniyya Nahda T; Akhmad Solikin (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Runway lighting is a critical facility that supports the safety and reliability of airport operations, particularly during nighttime operations and adverse weather conditions with limited visibility. This study aims to design and implement an Internet of Things (IoT)-based current and voltage monitoring system as an indicator of disturbances in a runway edge light prototype. The proposed system utilizes an ACS712 current sensor, a ZMPT101B voltage sensor, an ESP32 microcontroller, a 16x4 LCD display, and the Blynk platform. The monitored parameters include current and voltage, which are processed by the ESP32 and transmitted via a Wi-Fi network for real-time monitoring. The test results show that the prototype successfully measured voltage values ranging from 203 V to 220.5 V and current values ranging from 1.90 A to 2.03 A, with a monitoring success rate of 100%. The system successfully identified normal conditions, undervoltage, overcurrent, and electrical circuit interruption based on predefined thresholds of 209–231 V for normal voltage and 1.8–2.0 A for normal current. Data transmission to the Blynk dashboard achieved a 100% success rate with an average delay of 1.22 seconds. The developed prototype demonstrates the feasibility of real-time electrical parameter monitoring and preliminary disturbance indication for runway edge light models under laboratory testing conditions.